(untitled) (Journal on studies and research of academic knowledge, 2013)
With the increasing urbanization of cities occurs gradual soil sealing, which reduces considerably the volume of infiltrated water in the soil, increasing the flow of surface runoff and the risk of flooding in the lower sectors of the cities. In recent years there has been a dewlopment in the study of pervious concrete and its application in permeable paving as an alternative to reduce the surface runoff since it allows the infiltrated water through the surface for the final disposal in the soil. Under the benefits inherent in the use of this material, this investigation analyses the dosages of pervious concrete made with local materials available in Encarnación City and in turn, determines whether the characteristics of strength and permeability are within the requirements established by the ACI 522-R10. A total of 16 dosages were analyzed and compression strength and permeability tests were made in 96 specimens. The obtained result was a concrete of low to moderate strength (3,5 a 9,5 MPa) and high permeability (200 a 2000 L/min/m2), all within the values set by the standard mentioned above.